2003
DOI: 10.1056/nejmoa022066
|View full text |Cite
|
Sign up to set email alerts
|

Silent Brain Infarcts and the Risk of Dementia and Cognitive Decline

Abstract: Elderly people with silent brain infarcts have an increased risk of dementia and a steeper decline in cognitive function than those without such lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
1,392
9
53

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,055 publications
(1,503 citation statements)
references
References 31 publications
49
1,392
9
53
Order By: Relevance
“…Participants in the CARDIA (Coronary Artery Risk Development in Young Adults) brain MRI substudy who achieved more ideal CVH at ages 18 to 30 had larger brain volumes 25 years later, but they observed no associations with normal gray or white matter volume or abnormal white matter volume 24. WMHV, brain atrophy, and SBI are all important imaging biomarkers of brain aging and predictive of future risk of stroke and dementia across study populations 9, 10, 11. These brain changes have potential as brain health markers that can be used both clinically and in research studies as intermediate or surrogate outcomes to help identify at‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the CARDIA (Coronary Artery Risk Development in Young Adults) brain MRI substudy who achieved more ideal CVH at ages 18 to 30 had larger brain volumes 25 years later, but they observed no associations with normal gray or white matter volume or abnormal white matter volume 24. WMHV, brain atrophy, and SBI are all important imaging biomarkers of brain aging and predictive of future risk of stroke and dementia across study populations 9, 10, 11. These brain changes have potential as brain health markers that can be used both clinically and in research studies as intermediate or surrogate outcomes to help identify at‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the AHA has now defined optimal brain health by the Life's Simple 7 metric, there is very limited evidence regarding its impact on biomarkers of subclinical brain aging. Subclinical brain aging biomarkers, including white matter hyperintensities, silent brain infarct (SBI), and brain atrophy, are common in the population and important risk factors for stroke as well as cognitive decline and dementia 9, 10, 11. The potential association of Life's Simple 7 and these important subclinical imaging biomarkers of brain aging is largely unknown and the motivation for the current analysis.…”
mentioning
confidence: 99%
“…1205 Nevertheless, there is a possibility of long-term sequelae, given the association between silent cerebral infarcts and an increased long-term risk of dementia. 1217 While further work remains, the amount of progress is striking and will benefit our patients in the long term.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…Although the reported rates of clinically overt cerebrovascular events are relatively low (<2%),2, 4 58% of patients undergoing routine VT ablation procedures exhibit new brain emboli in postprocedural CMRI 5. Most of the CMRI‐detected ischemic lesions remained clinically silent, but recent studies have shown that these lesions might be associated with neurocognitive impairment and the development of dementia 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…Although the relevance of clinically silent periprocedural embolic lesions is unknown, the long‐term consequences of these lesions might have negative neurocognitive effects such as premature dementia 5, 6, 20. Most endovascular electrophysiological procedures such as CA of atrial fibrillation and, particularly, VT are associated with fairly long procedure durations compared with other interventional procedures (eg, coronary angiography, LAA closure, TAVR, and mitral valve repair with the MitraClip).…”
Section: Discussionmentioning
confidence: 99%